E agora? Eu preciso trabalhar: webdocumentário sobre como as trabalhadoras domésticas enfrentaram a pandemia em Uberlândia - MG. - Moretti, Victoria Kortbawi Sant’Anna Duarte (2022)
The present work records the production process of the web documentary “What now? I need to work”. It addresses how domestic workers in the city of Uberlândia (MG) faced the pandemic caused by the new coronavirus (COVID-19). The data for the script consolidation and configuration of the film narrative are the result of bibliographic research and document analysis. The film contains a selection of reports on what it was like to work during the pandemic to maintain family income, in addition to the testimony of health experts to talk about the virus. Through the juxtaposition of these different reports, it is possible to denote the need for public policies to discuss, protect and support this segment of the society, which received little support during the pandemic.